Clinical evaluation of P-glycoprotein inhibition by venetoclax: a drug interaction study with digoxin. (2nd September 2018) - Chiney, Manoj S.; Menon, Rajeev M.; Bueno, Orlando F.; Tong, Bo; Salem, Ahmed Hamed
Abstract: 1. Venetoclax is a novel, small molecule B-cell lymphoma-2 (BCL-2) inhibitor that has demonstrated clinical efficacy in a variety of haematological malignancies. Since venetoclax is an inhibitor of P glycoprotein (P-gp) transporter, a study was conducted in healthy, female volunteers to evaluate the effect of venetoclax on the pharmacokinetics of digoxin, a P-gp probe substrate. 2. Volunteers received a single oral dose of digoxin (0.5 mg) with or without a single oral dose of venetoclax (100   mg). Serial blood samples were obtained for pharmacokinetic assessments of digoxin and venetoclax and serial urine samples were obtained for measurement of digoxin concentrations. Safety was assessed throughout the study. 3. Coadministration of digoxin and venetoclax increased digoxin maximum observed plasma concentration (Cmax ) by 35% and area under the plasma-concentration time curve (AUC0–∞) by 9%. Digoxin half-life, renal clearance and the fraction excreted unchanged in urine remained relatively similar. The results of this study indicate that venetoclax can increase the concentrations of P-gp substrates. Narrow therapeutic index P-gp substrates should be administered six hours prior to venetoclax to minimise the potential interaction.